Stable large area organic solar cells realized by using random terpolymers donors combined with a ternary blend. Issue 23 (30th May 2019) - Xu, Xiaopeng; Bi, Zhaozhao; Ma, Wei; Zhang, Guangjun; Yan, He; Li, Ying; Peng, Qiang
Abstract : The combination of terpolymer and ternary blend strategies contributed to stable nonfullerene organic solar cells with improved absorption, energy and charge transfer as well as optimized morphology, resulting in a high PCE of 13.63% in small area devices and 11.43% in large area devices. Abstract : To develop efficient nonfullerene organic solar cells (NF-OSCs), it is important to utilize the absorption of each material component for realizing broad and strong absorption. Developing ternary blend structures is an effective strategy that employs three different materials to achieve complementary absorption spectra. Herein, for the first time, we used D–A1–D–A2-type random terpolymers to enhance the absorption of the ternary blend NF-OSCs. Combined with the merits of the ternary blend structure, efficient NF-OSCs containing one terpolymer donor and two different molecular acceptors were investigated in detail. The weak points of the optical absorption spectra depended largely on the DPP/BT molar ratio. The terpolymer with 0.3/0.7 molar ratio (DPP/BT) was the best candidate for filling those weak points and generating a strong and broad absorption peak. The best devices exhibited good stability with a PCE of 13.63%, which remained at 80% of the original even after 400 hours of storage. A high PCE of 11.43% could also be realized even in the large area device (1.0 cm −2 ). Our study provides a useful concept to improve the absorption ability and elevate the efficiency of NF-OSCs by integrating a terpolymer donors and a ternary blend structure.